DEVELOPMENT TRAINING FOR WEBSITE USER INTERFACE OF YAYASAN AL-JIHAD SURABAYA - Mukhtar Adinugroho; Rita Sari; Teguh Herlambang; Firman Yudianto (Universitas Airlangga, 2023)
This paper focused is Training in User Interface Development on the Al-Jihad Foundation Surabaya Website. The purpose of this research is to find out how to design a User Interface at the Al-Jihad Foundation Surabaya and develop a User Interface design related to the addition of features. The problem of this research is whether the user interface design used by the Al Jihad Surabaya Foundation is correct and correct. The method in this study uses a qualitative case study approach. Which is where the data collection technique comes from observation of research objects and direct interviews with staff of the Al-Jihad Foundation Surabaya. The conclusions drawn from this study are the user interface is used to increase comfort and convenience on the website of the Surabaya al-Jihad Foundation, in order to attract users' interest in accessing the Surabaya Al-Jihad Foundation website. Based on the results of the questionnaire, it shows 97% of respondents like the user interface on the new website.